2017
DOI: 10.1016/s1470-2045(17)30422-9
|View full text |Cite|
|
Sign up to set email alerts
|

Nivolumab in patients with metastatic DNA mismatch repair-deficient or microsatellite instability-high colorectal cancer (CheckMate 142): an open-label, multicentre, phase 2 study

Abstract: Summary Background Metastatic DNA mismatch repair–deficient/microsatellite instability–high (dMMR/MSI-H) colorectal cancer (mCRC) has a poor prognosis following conventional chemotherapy and exhibits high levels of tumour neoantigens, tumour-infiltrating lymphocytes, and checkpoint regulators, all features that correspond with response to programmed cell death receptor-1 (PD-1) blockade in other tumour types. Thus, nivolumab, a PD-1 immune checkpoint inhibitor, was evaluated in this population. Methods In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
1,694
8
19

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 2,234 publications
(1,880 citation statements)
references
References 31 publications
40
1,694
8
19
Order By: Relevance
“…In contrast, previous studies concerning treatment response from PD-1 or PD-L1 blockade in CRC report clinical benefit only for patients with MSI-high tumours, 12 , 13 possibly explained by the fact that MSI-high tumours generally carry a higher mutational load, resulting in a robust T cell response which can be exploited by relieving the negative pressure. Nevertheless, Droeser et al.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In contrast, previous studies concerning treatment response from PD-1 or PD-L1 blockade in CRC report clinical benefit only for patients with MSI-high tumours, 12 , 13 possibly explained by the fact that MSI-high tumours generally carry a higher mutational load, resulting in a robust T cell response which can be exploited by relieving the negative pressure. Nevertheless, Droeser et al.…”
Section: Discussionmentioning
confidence: 66%
“…11 In CRC, the clinical benefit of PD-1 or PD-L1 blockade remains uncertain, however, a few studies report a positive effect of anti-PD-1 antibodies in patients with microsatellite instability (MSI) high tumours 12 , 13 and anti-PD-1 therapies were recently approved by the U.S Food and Drug Administration for treatment of any type of advanced MSI-high cancer.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 However, only a small number of patients respond. 7,8 Therefore, it has been urgent to identify the best candidates for this therapy and explore novel targets to develop new treatment strategy. In this study, we found that the B7 and TNFR family genes were mutated, amplified or deleted in CRCs, which is consistent with previous studies in other cancer types, including breast cancer, head and neck cancer.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 MSI is a consequence of impaired DNA mismatch repair, resulting in mutation accumulations to create a rich source of tumor-specific neoantigens. 13 Some of which will be presented on the major histocompatibility complex (MHC), recognized as foreign by T cells, and thereby might stimulate lymphocytic reaction.…”
Section: Discussionmentioning
confidence: 99%
“…The approval of anti-PD-1 therapy for the treatment of adult and pediatric patients with MSI-H or dMMR solid tumors (pembrolizumab) or colorectal cancer (pembrolizumab and nivolumab) that has progressed, underscores the importance of considering other biomarkers that are not specific to the immune checkpoint pathway when making ICB therapy decisions [13]. Patients with MMR deficiency are associated with a higher mutational burden and tumor neoantigen load than MMR-proficient patients, and these features could be driving clinical benefit of ICBs [33,97,98]. In fact, tumor mutational burden, known to enhance neoantigen formation, has been shown to be associated with increased response to ICBs, and in some cases improved OS as well, across tumor types such as melanoma [99,100], NSCLC [101], and UC [54,56,102].…”
Section: Immunotherapeutics and Patient Selectionmentioning
confidence: 99%